Developing eFolio mobile (Android and iPhone-based) application: perspectives, experiences and challenges - Md Ghalib, Mohd. Feham; Sahrir, Muhammad Sabri; Mat Daud, Nuraihan; Hassan, Haslina; Mohin, Mohaida; Ayu, Media Anugerah (2013)
Advances in the mobile technology are ubiquitously a part of the lives among educators and students alike these days. We could use a communication device to share wide range of information with our relatives, friends, and colleague (MLearning, December 2010). In fact with the newer development in mobile technology, the use of hand phone can be extended not to only text-based messages but to also include rich multimedia experiences. The issue, however, that should be taken into account is how best we might use these resources to support teaching and learning processes given the fact that the use of mobile gadgets among our students and lecturers is almost very much pervasive (Thornton & Houser, 2004; Proctor & Burton, 2003; Colley & Stead 2003). The present research seeks to shed some light on the workable model for using and developing a mobile application for learning through electronic portfolio in particular, sharing various types of artifacts, reflective journal writing, learning experiences between the students and their peers in a more convenient way via mobile such as iPhone, iPad or android-based smart device. Since the main web platform is already available, the present project tends to explore further the prototype development and implementation of the mobile accessibility of the current platform. This obviously will equip the platform with an added value for the students and lecturer alike. It enriches their learning and teaching experiences as well as realizing them the true unleashed potential of communicating and sharing via the mobile approach. Prior to that, the need analysis of the end-users is conducted to know best the mode and style of interactivity that they might expect using mobile applications.